Protective headgear for soccer players: An overview - Gray, M.; Bain, J.; Willis, L. (The Sport Journal, 2009)
Protective headgear has been worn by thousands of American soccer players in youth leagues, high schools, colleges, and even professional leagues. While some current studies indicate that concussions occur among soccer players at a rate similar to that among football players, other studies contradict such results and the issue remains disputed. Moreover, studies disagree on whether heading the ball can cause concussions or long-term brain impairment. This article examines the causes and occurrence of head injuries in soccer and the possible role of protective headgear in preventing those injuries.